Imbibition damage in soybean seeds as affected by initial moisture content, cultivar and production location - Toledo, M. Z. [UNESP]; Cavariani, Cláudio [UNESP]; Franca-Neto, J. de B.; Nakagawa, J. [UNESP] (Ista-int Seed Testing Assoc, 2010)
Soybean seeds may show low germination when evaluated by the paper towel germination test due to high percentages of abnormal seedlings, typical of imbibition damage. This research evaluated the effect of initial seed moisture content (SMC) of different soybean cultivars and production locations on the occurrence of imbibition damage. Treatments consisted of seedlots of four cultivars (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA) 48, BRS 184, BRS 232 and BRS 245RR) from 4 Brazilian production locations (Ponta Grossa-PR, Londrina-PR, Maua da Serra-PR and Orlandia-SP). Seed moisture content was adjusted to 9%, 11%, 13%, 15% and 17% prior to the evaluation of imbibition damage. A completely randomized experimental design was used with four replications. Analysis of variance and mean comparison by the Tukey and the Dunnet tests (P <= 0.05) were applied for statistical analysis. It was concluded that the increase of seed moisture content is affected by cultivar and initial seed quality. Additionally, it was observed that imbibition damage is not detected when initial seed moisture is equal to or higher than 15%.